Assessing the impact of administrative delays on local government vehicle fleets (LGVF) downtime in South Africa - Nyamutora, Tinashe (Stellenbosch : Stellenbosch University, 2025)
Nyamutora, T. 2025. Assessing The Impact of Administrative Delays on Local Government Vehicle Fleets (LGVF) Downtime in South Africa. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/5ed4c803-5f95-4174-abe6-1891b70e6392